Studi Geologi Bawah Permukaan Menggunakan Core Logging Dan Water Pressure Test: Studi Kasus Bendungan Lolak Bolaang Mongondow - Nani Mardiani; Sri Maryati; Ronal Hutagalung; Muhammad Kasim (Jambura Geoscience Review, 2022)
North Sulawesi has one large dam located in Pindol Village, Lolak District. The research objective was to determine the lithology of the bedrock of dam foundation, rock class, and subsurface permeability of the dam. The method used in this research is core logging analysis and water pressure test. The bedrock foundations of the dam consist of andesite units, shale units, sandstone units which are included in the Sedimentary Facies Tinombo Formation and Volcanic Tinombo Formation. The formations are included in the Eocene to Early Oligocene Eocene and deposited in the deep marine environment. The foundation rock class is predominantly CM class (rather soft and fairly weathered rock), the rock quality of design is poor-medium characterized by the presence of broken cores and easily crushed in some parts. Lolak Dam has 6 permeability zones, namely very high, high, medium, moderate, low, and very low permeability with an average lugeon value of 4.43 liters/minute. The standard of lugeon value for the dam foundation is Lu3, so it is necessary to repair the drill points on the pilot hole which has a lugeon value of 3 (low, moderate, medium, high, and very high permeability zones) to increase the capacity foundation rock.